APPLICATION OF METHODS MULTI-CRITERIA DECISION FOR EVALUATION THE QUALITY OF PUBLIC TRANSPORT (Perner's Contacts, 2011)
The article deals with methods multi-criteria decision can be applied forevaluation the quality of public transport. The article is an analysis of methods ofdetermining weights of criteria, methods of multi-criteria decision and theirevaluation in terms of their use for evaluation the quality of public transport.
Keywords: public transport; evaluation the quality; methods multi-criteria decision